Demand-driven inventory optimization and replenishment : creating a more efficient supply chain - Davis, Robert A., 1947- (Wiley, 2016)
"This new edition provides a focused message on how inventory optimization effects specific business verticals through improved metrics. It reviews the fundamentals of inventory optimization so that practitioners can attain a demand driven supply as well as provides a business perspective of why present inventory systems sub-optimize the supply chain and faulty replenishment processes lead to wasted time and effort. Readers come away with a good understanding of why optimized inventory and replenishment helps overcome in-system weaknesses and deliver results. The book lays out a historical view of the three major supply chain efforts of the last 30 years (i.e., Just in Time (JIT), Efficient Consumer Response (ECR), and Collaborative Forecasting, Planning and Replenishment (CPFR). It then discusses mathematical shortcuts set up in the transitional and supply chain management systems that make it very difficult for companies to attain "supply chain excellence". A discussion of how multi-echelon inventory optimization and replenishment enables the installed systems go from a sequential, "islands of efficiency" approach to a systematic distribution system working as a complete network is also given. Case studies are provided throughout the book. New topics covered include: inventory performance, scenario updates and replenishment; examples of why promotional product flow hurts supply chains; and discussion of industry verticals (What are the relevant issues in industry verticals that would prompt someone to look at inventory optimization?), business initiatives (what are today's initiatives that are relevant to inventory optimization?), and metrics (what are the underlying business KPI's that can be improved by using inventory optimization?).